020 Psychogenic/dissociative/functional facial symptoms—a case report. Issue 10 (24th September 2010) - Stone, J; Carson, A
Abstract : Background: There was debate in the 19th century regarding the question of whether there was such a thing as hysterical paralysis of the face. Charcot thought it did not occur but Janet, Gowers and others reported cases. It has only been rarely reported since. Case Report: We report the case of a 40 year old woman with a 3 year history of right sided weakness initially attributed to lupus because of a diagnosis of discoid lupus affecting the skin. She also had widespread muscle pain, fatigue and recurrent depressive symptoms. On review the weakness was clearly functional/psychogenic in distribution with a positive Hoover's sign. MRI and CSF analysis were normal and there was no support for a diagnosis of lupus. 2 years into her illness she developed recurrent episodes of right "pseudoptosis" with contraction of orbicularis oculis and oris which gave an impression of right facial weakness. She described unilateral photophobia in the right eye. The facial symptoms could be induced by shining a light in her right eye but not her left (video will be shown). We report this case in the context of features of six other cases of psychogenic/functional hemifacial symptoms. Conclusion: It is possible to have a functional/psychogenic symptoms in the face, typically in association with weakness of the ipsilateral arm and leg and often with photophobia in the affected eye. However, the apparent weakness is a result of excessive contraction of orbicularis oris/oculis or platysma rather than weakness. This case also illustrates the important role that conditioned responses can play in patients with functional/psychogenic neurological symptoms.